Role of saphenoperitoneal shunt in management of refractory ascites - Ibrahim SMA; Harunarashid H (Department of Surgery, UKM Medical Centre, 2011)
Refractory ascites is difficult to treat by restriction of salt and repeated paracentesis which have been the mainstay of treating it for a long time. Sapheno-peritoneal shunts have been performed in patients with refractory ascites . Here, we evaluated the use of saphenous vein to be anastomosed to the peritoneam to drain the refractory ascites. Nine patients (7 male, median age 45 years, range 17 - 69) with tense refractory ascites associated with liver cirrhosis, perioprtal fibrosis and end stage renal diseases underwent sapheno-peritoneal anastomosis by mobilizing and rotating the proximal vein in order to be anastomosed to peritoneum in the lower abdomen . All procedures were performed under local anaesthesia. Thirty-day mortality was 22% (2) patient. Morbidity included fluid leakage in 1 (11%), and wound infection in 1 (11%). Hospital stay (median) was 16 days (range 11 to 23). In the short term (median of 2 months) significant reduction in body weight and abdominal girth was seen in 9 (90%), 6 (60%) were not on diuretics while 3 (30%) continued to remain on reduced doses of diuretic. Furthermore, 7 (70%) did not require paracentesis. At 2-year follow-up, 5 (45%) patients died and 3 succumbed during follow-up. The remaining 3 were all in active employment, 1 was off diuretics, and 2 were on reduced doses. All 3 patients maintained reduced body weights and abdominal girths compared with preoperative values. Saphenous-peritoneal shunt appears a simple, safe, and cost effective method of achieving long-term control of refractory ascites. The use of autogenous shunt is an added advantage over prosthetic shunts for drainage of ascitic fluid.